Probiotics and Functional Gastrointestinal Disorders in Pediatric Age: A Narrative Review - Capozza, Manuela; Laforgia, Nicola; Rizzo, Valentina; Salvatore, Silvia; Guandalini, Stefano; Baldassarre, Mariella (Frontiers in Pediatrics, 2022)
Assessment and management of pain are essential components of pediatric care. Pain in pediatric age is characterized by relevant health and socio-economic consequences due to parental concern, medicalization, and long-term physical and psychological impact in children. Pathophysiological mechanisms of nociception include several pathways in which also individual perception and gut-brain axis seem to be involved. In this narrative review, we analyze the rational and the current clinical findings of probiotic use in the management of functional gastrointestinal disorders (FGID) in pediatric age, with special focus on infantile colic, irritable bowel syndrome, constipation, and gastroesophageal reflux. Some specific probiotics showed a significant reduction in crying and fussing compared to placebo in breastfed infants with colic, although their exact mechanism of action in this disorder remains poorly understood. In irritable bowel syndrome, a limited number of studies showed that specific strains of probiotics can improve abdominal pain/discomfort and bloating/gassiness, although data are still scarce. As for constipation, whilst some strains appear to reduce the number of hard stools in constipated children, the evidence is not adequate to support the use of probiotics in the management of functional constipation. Similarly, although some probiotic strains could promote gastric emptying with a potential improvement of functional symptoms related to gastroesophageal reflux, current evidence is insufficient to provide any specific recommendation for the prevention or treatment of gastroesophageal reflux. In conclusion, probiotics have been proposed as part of management of pain in functional gastrointestinal disorders in pediatric age, but mechanisms are still poorly understood and evidence to guide clinical practice is currently inadequate.